Ruderal Resilience: Applying a Ruderal Lens to Advance Multispecies Urbanism and Social-Ecological Systems Theory - Kennedy, Christopher (Frontiers in Built Environment, 2022)
As global urbanization accelerates, cities have become complex and hybridized, and increasingly host to novel urban landscape forms such as informal greenspaces or novel ecosystems that support ruderal and spontaneous vegetation. Researchers have documented the ecosystem services or benefits these systems provide to humans and other organisms, as well as the tradeoffs or disservices associated with biotic globalization. Yet despite evidence of their benefit, fragmented knowledge and biased views of novel ecological forms contribute to an underestimation of their social-ecological role in cities and potential for serving as a model for resilient and nature-based urban design and planning. The social-ecological systems discourse has provided crucial insights into understanding these emerging conditions, yet may benefit from an attunement to a multispecies perspective, an ecosystem-based approach to urban planning and governance that integrates their diverse needs and functions of multiple species into planning and decision-making processes. This article explores the potential social-ecological role of novel and ruderal ecologies in facilitating a transition toward a multispecies urbanism and new approaches to resilience thinking, referred to as ‘ruderal resilience’. The article synthesizes recent research in social-ecological systems and resilience theory, multispecies studies, and novel and ruderal ecosystems to consider how the ecological functions, traits, and adaptive capacities of ruderal systems may be leveraged to reinvigorate relationships with urban nature and advance social-ecological systems theory.